Implementing white hat search engine technique in e-business website - Roslina, Abd Hamid; Nur Shahirah, M. F. (ACM, 2019)
In today’s worldwide of e-business marketing, there are demanded searching engine. Hence, Search Engine Marketing (SEM) with paid and non-paid searching. Data or information about an unknown subject is usually searched for the first page of search engines. The purpose of the research is to analyze, design and develop a domain website using White Hat SEO techniques. The collected data include the website URL, some keywords or keyword groups that define the content of the web site, the code structure that forms the web page and also links provided on the web site. It is important to move a web page to top lists of search engines in order to increase visibility thus getting t h e highest number of visitors. The website published using a chosen platform verified by Google Search Console and tested in Google Search engine. The website achieving high ranking results in Google Search which is in the top three of the first page in Google search. The result obtained shows that the White Hat SEO technique was correctly implemented.